Predictive Indicators of Psychological Inflexibility in Women Engaged in High-Risk Romantic Relationships - Morales, Luis (Psychology of Woman Journal, 2025)
Objective: This study aimed to identify the core psychological patterns and experiential indicators that predict psychological inflexibility in women involved in high-risk romantic relationships. Methods and Materials: A qualitative research design was employed, utilizing semi-structured, in-depth interviews with 20 women from Kenya who were currently or recently engaged in romantic relationships characterized by emotional, psychological, or physical risk. Participants were recruited through purposive sampling, and interviews were conducted until theoretical saturation was reached. Data were transcribed verbatim and analyzed using thematic analysis in NVivo 14 software, following Braun and Clarke’s six-phase approach. The trustworthiness of the analysis was ensured through member checking, peer debriefing, and an audit trail. Findings: Thematic analysis revealed four overarching categories reflecting the predictive indicators of psychological inflexibility: (1) Cognitive Rigidity and Maladaptive Beliefs, including overgeneralization, black-and-white thinking, and fatalistic worldviews; (2) Emotional Dysregulation and Experiential Avoidance, such as emotional suppression, fear of expression, and numbing; (3) Relational Dependency and Identity Diffusion, marked by fused identities, fear of abandonment, and lack of assertiveness; and (4) Trauma History and Psychological Vulnerability, including unresolved childhood trauma, repetition of abusive patterns, and hypervigilance in intimacy. Participants’ narratives revealed how these patterns sustained psychological inflexibility and impaired their ability to exit or reframe harmful relationships. Conclusion: Psychological inflexibility in women engaged in high-risk romantic relationships is shaped by a convergence of cognitive rigidity, emotional avoidance, relational enmeshment, and unresolved trauma.